Audit of Antipsychotic Monitoring in an Old Age Community Mental Health Team in Accordance With NICE Guidelines - Serife Dilara Yozgatli; Felix Clay (BJPsych Open, 2025)
Aims: Antipsychotic monitoring is crucial for identifying and managing side effects, improving treatment compliance, and reducing risks associated with long-term use. NICE guidelines recommend routine monitoring to enhance quality of life and prevent disengagement due to adverse effects. This audit assesses compliance with these guidelines within an Old Age Community Mental Health Team (CMHT). This was also discussed in MDT, as well as with patients and carers to have a better understanding of patient experience and how we can enhance antipsychotic monitoring.